Bidirectional recovery patterns of Mojave Desert vegetation in an aqueduct pipeline corridor after 36 years: II. Annual plants. (November 2015) - Berry, Kristin H.; Mack, Jeremy S.; Weigand, James F.; Gowan, Timothy A.; LaBerteaux, Denise
Abstract: We studied recovery of winter annual plants in a 97-m wide disturbed aqueduct corridor in the Mojave Desert 36 years after construction. We established plots at 0, 20, and 40 m from the road verge at the corridor center and at 100 m in undisturbed vegetation. We recorded 47 annual species, of which 41 were native and six were exotic. Exotic species composed from 64 to 91% of total biomass. We describe a bilateral process of recovery: from the road verge to the outward edge of the corridor and from undisturbed habitat into the corridor. Native annual plants significantly increased in richness from road verge to undisturbed vegetation, but not in density, biomass, or cover. In contrast, exotic annual plants increased in density, biomass, cover and richness with increasing distance from the road verge. The species of colonizing shrubs and type of canopy cover affected density, biomass, and richness of annuals. Species composition of native annuals differed significantly by distance, suggesting secondary succession. In general, native annuals were closer to achieving recovery on the 40-m plots than at the road verge. Recovery estimates were in centuries and dependent on location, canopy type, and whether considering all annuals or natives only. Highlights: We studied recovery of annual plants in the Mojave Desert 36 years after disturbance. The recovery process in the 97-m wide disturbance corridor was bilateral. Composition of native annual plants differed by location in the disturbance corridor. Native annual plants may require centuries to recover composition after disturbance. We found evidence of secondary succession in Mojave Desert annual plants.